Analisis Atribut Produk Wisata Sejarah Di Candi Tanjung Medan - Iqbal Habibi; Dwi Pratiwi Wulandari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
Indonesia is the largest archipelagic country in the world which has cultural diversity. The development of the tourism sector in Indonesia continues to be carried out in various regions until now, one of which is the Tanjung Medan Temple. This research aims to analyze the attributes of historical tourism products at Tanjung Medan Temple. This research uses a descriptive method with a qualitative approach, with data collection through interviews, observation and documentation. Using qualitative descriptive data analysis that describes the attributes of historical tourism products at Tanjung Medan Temple. Determining research informants used snowball sampling with a total of 11 informants, but if no conclusions were found, the researcher had the right to add further informants, with the criteria being figures from the Tourism Office, managers, ninik mamak, the community, visitors to the Tanjung Medan temple. The results of the research show that cultural products are in the form of movable cultural heritage in the form of linga yoni, peripih, and jars made of clay. The narrative product at Tanjung Medan Temple consists of a tour guide and interpretation panels. Tourist products consist of travel scenarios and product packaging. Destination products consist of main attractions, accommodation, transportation, restaurants, souvenir shops, infrastructure. It can be concluded that the results of the document study during pre-research show that there are no tourist packages available in West Sumatra which makes Tanjung Medan Temple one of the destinations for tourist visits. So it is necessary to develop historical tourism product attributes at Tanjung Medan Temple.